Classifying donor strengths of dipyrrinato/aza-dipyrrinato ligands. Issue 22 (9th May 2019) - Diaz-Rodriguez, Roberto M.; Robertson, Katherine N.; Thompson, Alison
Abstract : A Pd-NHC probe and 13 C NMR spectroscopy provide insight regarding ligand donor strength of dipyrrinato and aza-dipyrrinato ligands. Abstract : A parameter is reported by which to use 13 C NMR chemical shifts to measure and predict the donor capabilities of N^N dipyrrinato and aza-dipyrrinato ligands chelating in L^X fashion. The results enable the rationalisation of the properties of these ligands and their complexes, as well as enable rational design incorporating both steric and electronic considerations when tuning to effect desired applications. Complexes containing these ligands are prevalent due to their desirable photophysical properties such as high chemical stability, resistance to photodegradation, strong absorbance, and ease of chemical modifiability.